Grounding Peace through the Word of God and Bearers of the Word: A Christian-Muslim Comparative Theology - Parihala, Yohanes (Wawasan: Jurnal Ilmiah Agama dan Sosial Budaya, 2022)
The theological debate between Islam and Christianity has been going on for centuries. The debate covered various theological issues such as the meaning of the revelations to the Prophet Muhammad, the revelations of the Qurâ€™Än, then the divinity of Jesus, the Incarnation of Jesus, the Trinity, and so on. The theological debates between the two religions often lead to contradictions and conflicts. This article aims to carry out a comparative study of critical theological issues, namely the Incarnation of Jesus and the Revelation of the Qur'an as the Word of God, and the meaning of the roles of Mary and Muhammad as carriers of God's Word. I use comparative analysis to seek a mutual understanding of two different religious concepts and traditions. From the results of the analysis, I propose that the main thesis is the theological vision of the revelation of God's Word both through incarnation and revelation of the Qur'an is to ground God's peace.